DEVELOPMENT OF QUALITY INSTRUMENTS AND DATA COLLECTION TECHNIQUES - Sukmawati, Sudarmin, Salmia (Universitas Pakuan, 2023)
Data collection methods and tools are the techniques and tools used in research to collect various data which are processed quantitatively or qualitatively, then arranged systematically. Data collection is defined as research activities that aim to collect field data needed to answer research questions in qualitative research or to test hypotheses in quantitative research. Research instruments are tools that use various types of information in research to be collected, processed quantitatively or qualitatively and then arranged systematically. Qualitative researchers as human instruments function to determine research focus, select informants as data sources, collect data, assess data quality, analyze data, interpret data and make conclusions on all stimuli from the environment that must be estimated to be meaningful or not for research. Quantitative research uses test instruments, non-test instruments and test inventories. For disclosure of facts to become data, the instruments used must be of good quality in the sense of being valid and reliable so that the data obtained will be in accordance with the facts or circumstances when collecting, studying, studying the problem under study.